Geocasting with guaranteed delivery in sensor networks. - Stojmenovic, I.
In a geocasting problem, a message is sent from one node to all the nodes located in a designated region. For example, a monitoring center needs to contact all active sensors within a monitored area to either gather data from them periodically or provide its location to sensors covering a certain area for event reporting. Intelligent flooding methods exist for this task when all active sensors belong to the monitored area. However, when a particular area containing only a small subset of active sensors needs to be monitored, the problem reduces to geocasting. Most existing geocasting solutions are shown not to guarantee delivery. We describe three approaches to guarantee delivery. Two of them are face traversal schemes, based on depth-first search of the face tree and traversal of all faces that intersect the border of the geocasting region, respectively. In the entrance zone multicasting-based approach, the monitoring center divides the entrance ring of a geocast region into zones of diameter equal to the transmission radius. The problem is decomposed into multicasting toward the center of each zone, and flooding from these nodes. Improvements to all methods can be made by applying neighbor or area dominating sets and coverage, and converting nodes that are not selected to sleep mode. All solutions that guarantee delivery are reported here for the first time (except a message inefficient version of the face tree traversal scheme).
Keywords: Entrance-zone multicasting-based approach; Face transversal scheme; Face tree; Geocasting; Sensor network